Gossypin Regulated Doxorubicin-Induced Oxidative Stress and Inflammation in H9c2 Cardiomyocyte Cells - YAZĞAN, Yener; YAZĞAN, Betül (Medical Records - International Medical Journal, 2024)
Aim: Doxorubicin (DOX), an anthracycline, is widely used in chemotherapy due to its effectiveness in fighting many cancers. Experimental and clinical studies prove that this drug damages non-targeted tissues (including cardiomyocytes) and reduces patients' quality of life during and after DOX treatment. The discovery of potent compounds as a protective tool to slow cardiomyocyte damage during the use of anti-cancer drugs such as DOX is crucial for both more effective cancer treatment and to improve patient's quality of life. Gossypin (GOS) is a flavonoid with several important properties, such as anti-cancer, analgesic, antioxidant, and anti-inflammatory. GOS shows supportive effects against oxidative stress and inflammation by activating antioxidant defense enzymes. Material and Method: For the study, four groups were formed from H9c2 embryonic cardiomyocyte cells as Control, DOX (1 μM, 48 h), GOS25 (25 µg/ml, 48 h), and GOS50 (50 µg/ml, 48 h). In the study, Total antioxidant and oxidant status (TAS and TOS), levels of the inflammatory cytokines IL 1 beta and 6, and TNF α, lipid peroxidation levels as malondialdehyde (MDA), glutathione peroxidase (GSHPx), and glutathione (GSH) levels in the H9c2 embryonic cardiomyocyte cells were determined. Results: The results showed that DOX treatment caused cell toxicity in the embryonic cardiomyocyte cells and increased TOS, IL 1 beta and 6, TNF α, and MDA levels while decreasing TAS, GSH, and GSHPx levels. This situation improved with GOS treatment. Conclusion: As a result, it was determined that GOS treatment showed a protective effect in the DOX-induced cell toxicity model in H9c2 embryonic cardiomyocyte cell lines.
Keywords: Oxidative Stress; Inflammation; H9c2 cardiomyocyte cell; Gossypin; Doxorubicin; İnsan Biyofiziği; Human Biophysics; 3. Good health